Mathematical Problem Solving Ability Viewed from Students' Mathematical Disposition - Idris Fadillah; Wahyudin Wahyudin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Mathematics is an instrument for solving problems in life. So, ability to solve mathematical problems is one of the most important skills. Practitioners of education do different approaches to develop the mathematical problemsolving ability of students. Efforts have been made such as an attractive learning model and providing external motivation. Most students, however, were unable to finish and prepare to solve mathematical problems in daily life. This is due to the belief that mathematics is not linked with life, anxiety in solving non-routine problems, and feelings of complacency that contribute to low motivation for students. The aim of this research is to gain an overview of the mathematical problemsolving skills of students in terms of students' mathematical dispositions. This research method is qualitative with a case study approach and this research was carried out on 35 grade XI students from a high school in the district of Indragiri Hulu. This research showed that students with high mathematical dispositions were able to apply indicators of problemsolving steps well, students with moderate mathematical dispositions were not able to properly apply indicators of mathematical problemsolving steps, and students with low mathematical dispositions found it difficult to understand the given mathematical problems. So, we concluded that students with good mathematical dispositions can well apply indicators of mathematical problemsolving steps